The effect of previous employment experience and entrepreneurship exposure on entrepreneurship intentions of college level students - research - Rambe, P.; Ndofirepi, T.M. (Journal of Contemporary Management, 2017)
Sections of the growing body of literature on the influence of entrepreneurship education on the entrepreneurship intentions (EI) of students tend to speculate about the effect of students’ previous employment experience and entrepreneurship exposure on their intentions to engage in entrepreneurship. Such speculation can be attributed to the indiscriminate treatment of the effect of prior entrepreneurship experiences and being employed on EI and the erroneous assumption that exposure to entrepreneurship education naturally translates into a desire to partake in entrepreneurship activities after undergoing the instructional programme. The researchers explored whether students with formal employment experience and those exposed to entrepreneurship (e.g. through family business) prior to undergoing entrepreneurship education had EI that are different from that of who had not been employed and/or exposed to entrepreneurship before. Drawing on a quantitative approach and a survey research design, the study examined the effect of entrepreneurship exposure and previous employment experience on the EI and antecedents of the EI of students in an economically challenged country. The findings of the study revealed that, although an overwhelming majority (80.5%) of students intended to engage in entrepreneurship, significant differences in EI levels persisted between those students who were employed prior to their entrepreneurship education and those who had not been employed. However, mixed results were reported amongst respondents who had different entrepreneurship backgrounds. A key implication of this study is the need to tailor entrepreneurship education programmes to the needs of participants with different employment and entrepreneurship experiences rather than take a one-size-fit-all approach.
Published Article
Keywords: Entrepreneurship intentions; Previous employment experience; Previous entrepreneurship exposure